TATA KELOLA USAHA PETERNAKAN DI ERA GLOBAL: STRATEGI ADAPTIF DAN BERKELANJUTAN BAGI UMKM PETERNAKAN UNGGAS DI KABUPATEN PASURUAN, JAWA TIMUR - Susanto, Ari; Suprihandari, Miya Dewi; Sadiqin, Amin (Penerbit Lafadz Jaya, 2026)
Globalization creates challenges and opportunities for poultry farming MSMEs in Pasuruan Regency, East Java, in terms of market competition, cost pressures, and demands for animal welfare and environmental standards. This study aims to analyze adaptive and sustainable governance strategies that MSMEs can adopt to improve their competitiveness and business resilience (Gerber, P. J., et al., 2013). The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 12 key informants consisting of MSME owners, feed supplier partners, and representatives of related agencies, field observations, and reviews of policy documents. The findings indicate that the main adaptive strategies include the adoption of simple technologies such as a modified closed house system for energy efficiency, vertical integration with feed supplier partners, and diversification of processed products. Meanwhile, sustainability strategies are realized through the implementation of collaborative biogas-based waste management and local halal certification to expand market access. However, significant obstacles are still encountered in limited capital, access to modern management training, and fluctuations in global feed prices. The novelty of this research lies in the integration of adaptive strategies based on simple technological efficiency with a collaborative sustainability approach based on a circular economy in the context of local poultry farming MSMEs, which has not been specifically discussed in previous studies at the regional level. This study recommends the need for multi-stakeholder policy synergy that strengthens access to financing, supporting infrastructure, and sustainable mentoring based on local wisdom. The implementation of this strategy is expected to form a model of poultry farming business governance that is resilient in facing global dynamics without ignoring the principles of a circular economy and the socio-culture of local communities.